Acute Effect of Electronic Cigarette-Generated Aerosol From Flavored CBD-Containing Refill Solutions on Human Bronchial Epithelial Cells - Leigh, Noel J.; Goniewicz, Maciej L. (Frontiers in Physiology, 2020)
Introduction Although electronic cigarettes (e-cigarettes) were originally developed to deliver aerosolized nicotine to lungs, recent data has shown that consumers also use them for inhalation of other drugs, including cannabidiol (CBD). The aim of this study was to test the acute inhalation toxicity of flavored CBD-containing aerosols emitted from e-cigarettes. Methods Bronchial epithelial cells (H292) cells were exposed to aerosol generated from e-cigarettes refilled either with 1) propylene glycol solvent only (PG, control) 2) commercially purchased unflavored solution with CBD or 3) commercially purchased solutions with and without CBD and with different flavors. The in vitro toxicological effects were assessed using the following methods: 1) trypan blue exclusion assay (cell viability), 2) neutral red uptake assay (metabolic activity) and 3) ELISA (concentrations of inflammatory mediators). Results Most flavored products with or without CBD were cytotoxic as compared to the air control. Overall, aerosols with CBD were more cytotoxic than aerosols without CBD irrelevant of the flavoring used in the product. Although, unflavored aerosols containing CBD in PG were significantly more cytotoxic than aerosols containing only PG, not all flavored products containing CBD were significantly more toxic than the same flavored products without CBD. Most CBD containing products significantly increase the concentration of cytokines released as compared to the same flavored products without CBD. Conclusions Different flavors show different cytotoxic effects in CBD-containing e-cigarettes. Aerosols emitted from CBD containing e-cigarettes were more cytotoxic than those emitted from CBD free e-cigarettes.